Desarrollo De Aplicación Móvil Para Brindar Información Asistencial Al Motociclista Motohelp (2021)
More than sixteen million (16'000,000.00) vehicles circulate in Colombia motorized vehicles, where 59% corresponds to a motorcycle according to figures obtained by the magazine Motor in its publication of January 21, 2021 https://www.motor.com.co/actualidad/industria/runt-dice-2020-peor-ano-matriculas-traspasoscarros-colombia-ultimos-4-anos/35614, therefore, the largest number of vehicles that circulate In Colombia they are motorcycles, only in the city of Bogotá 54% of the vehicles that transit correspond to a motorcycle.